Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Solve for one of the variables in the first equation (in this case, I will solve for X):
X = Y + 3
Then use that value of X in the second equation to solve for Y:
X + 3Y = 9
(Y + 3) + 3Y = 9
4Y + 3 = 9
4Y = 6
Y = 1.5
Use the value of Y we just found in the X equation we created:
X = Y + 3
X = 1.5 + 3
X = 4.5
Therefore X = 4.5 or 9/2 and Y = 1.5 or 3/2.
X = Y + 3
Then use that value of X in the second equation to solve for Y:
X + 3Y = 9
(Y + 3) + 3Y = 9
4Y + 3 = 9
4Y = 6
Y = 1.5
Use the value of Y we just found in the X equation we created:
X = Y + 3
X = 1.5 + 3
X = 4.5
Therefore X = 4.5 or 9/2 and Y = 1.5 or 3/2.
X - y = 3 is the same as x=3+y
3+y+3y = 9
3+4y=9
4y=9-3
4y=6
y=6/4
y=3/2
x-(3/2)=3
x=3+(3/2)
x=6/2+3/2
x=9/2
3+y+3y = 9
3+4y=9
4y=9-3
4y=6
y=6/4
y=3/2
x-(3/2)=3
x=3+(3/2)
x=6/2+3/2
x=9/2
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.